Effects of aging on the stress-induced martensitic transformation and cyclic superelastic properties in Co-Ni-Ga shape memory alloy single crystals under compression. (March 2022) - Lauhoff, C.; Reul, A.; Langenkämper, D.; Krooß, P.; Somsen, C.; Gutmann, M.J.; Pedersen, B.; Kireeva, I.V.; Chumlyakov, Y.I.; Eggeler, G.; Schmahl, W.W.; Niendorf, T.
Abstract: Co-Ni-Ga shape memory alloys attracted scientific attention as promising candidate materials for damping applications at elevated temperatures, owing to excellent superelastic properties featuring a fully reversible stress-strain response up to temperatures as high as 500 °C. In the present work, the effect of aging treatments conducted in a wide range of aging temperatures and times, i.e. at 300–400 °C for 0.25–8.5 h, was investigated. It is shown that critical features of the martensitic transformation are strongly affected by the heat treatments. In particular, the formation of densely dispersed γ'-nanoparticles has a strong influence on the martensite variant selection and the morphology of martensite during stress-induced martensitic transformation. Relatively large, elongated particles promote irreversibility. In contrast, small spheroidal particles are associated with excellent functional stability during cyclic compression loading of 〈001〉-oriented single crystals. In addition to mechanical experiments, a detailed microstructural analysis was performed using in situ optical microscopy and neutron diffraction. Fundamental differences in microstructural evolution between various material states are documented and the relations between thermal treatment, microstructure and functional properties are explored and rationalized. Graphical abstract: Image, graphical abstract